DAMPAK E-SECURITY DAN RISK PERCEPTION TERHADAP E-TRUST NASABAH PENGGUNA E-BANKING: PERAN LITERASI KEUANGAN - Dewi, Nadia Ayu Saraswati; Prasetyo, Agung Slamet (Media Mahardhika, 2025)
E-banking has become an essectial part of daily financial transactions, making trust in the system a critical factor in its usage. However, concerns about security and the perceived risks of using e-banking services may influence customers trust in the platforms. This study explores the impact of e-security and risk perception on e-trust among e-banking service users, with the moderating variable being financial literacy. The research adopts a quantitative methodology with a descriptive approach. Data was gathered using a non-probability sampling method through questionnaires distributed to 105 bank customers utilizing e-banking services in the Special Region of Yogyakarta. Hypotheses were tested using Moderated Regression Analysis (MRA) and Multiple Regression Analysis through SPSS. The findings reveal that e-trust is significantly impacted by both e-security and risk perception. Additionally, financial literacy is shown to moderate the connection between e-security and e-trust but not the connection between risk perception and e-trust.